Fertilización de la papa (Solanum tuberosum L.) en los suelos andasoles del departamento de Nariño, Colombia. - Wieczorek P, A.E.; Muñoz Araque, R. de J. (Instituto Colombiano Agropecuario, 2018)
Papa-Solanum tuberosum